2018
DOI: 10.3329/jbcps.v36i3.37037
|View full text |Cite
|
Sign up to set email alerts
|

Case Report of Scrub Typhus

Abstract: Scrub typhus is an acute, febrile, infectious illness that is caused by Orientia tsutsugamushi. Scrub and murine endemic typhus infections are under-diagnosed causes of febrile illness across the tropics, and it is not known how common they are in Bangladesh. Here reporting a case who presented with high grade fever for 7 days associated with headache, abdominal discomfort, cough and receiving inj ceftriaxone for 2 days considering as a case of enteric fever. Forty-eight hours after admission, the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In spite of significant serosurveillance reports [2][3][4] and clinical recognition of cases, rickettsial fevers are only occasionally reported in literature in or from Bangladesh. 5,6 The largest series published in 2007 revealed that clinical presentation is indistinguishable from other common causes of fever like viral and enteric fevers. 5 Presence of typical eschar in scrub typhus is also an uncommon feature.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of significant serosurveillance reports [2][3][4] and clinical recognition of cases, rickettsial fevers are only occasionally reported in literature in or from Bangladesh. 5,6 The largest series published in 2007 revealed that clinical presentation is indistinguishable from other common causes of fever like viral and enteric fevers. 5 Presence of typical eschar in scrub typhus is also an uncommon feature.…”
Section: Discussionmentioning
confidence: 99%